Fast Response Garda Ampuh dalam Penanganan Anak Muda Putus Sekolah di Banyuwangi - Ilham Nur Kholiq (IAI Darussalam, 2019)
The achievements and innovations developed by Banyuwangi District turned out to have many problems in the midst of the community, such as poverty, education (out of school children) who needed good handling. Based on observations and information obtained by researchers there are 10 sub-districts in Banyuwangi District, where the highest number of school dropouts is Rogojampi, Glagah, Tegaldlimo, Banyuwangi City. Gambiran, Kalipuro, Muncar, Kalibaru, Wongsorejo, and Singojuruh. The method used in this study is a qualitative method with descriptive analysis techniques. The data collection techniques using observation, interviews, and documentation. And the data sources are children who experience school dropouts, the Education Office, Tegadlimo UPTD and archives of school dropouts in Kecamatan Teglimlimo. The results of this study indicate, that the factors of school dropouts in Tegadlimo sub-district, Kalipait Village, Kendalrejo and Purwoagung are economic factors, leaving their parents to leave as migrant workers or die, access roads, juvenile delinquency and the environment. Whereas the government's way of dealing with school dropouts is by providing pocket money, smart Banyuwangi transport money, effective garda savings, being included in the package A, B and C equality program, KIP (Kartu Indonesia Pintar) program and SAS Program (Siswa asuh Sebaya).